2006
DOI: 10.1111/j.1528-1167.2006.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Long‐term Seizure Susceptibility and the Complex of PSD‐95 with NMDA Receptor from Animals Previously Exposed to Perinatal Hypoxia

Abstract: Summary:Purpose: Perinatal hypoxia is an important cause of brain injury in the newborn and has consequences that are potentially devastating and life-long, such as an increased risk of epilepsy in later life. The postsynaptic density (PSD) is a cytoskeletal specialization involved in the anchoring of neurotransmitter receptors and in regulating the response of postsynaptic neurons to synaptic stimulation. The postsynaptic protein PSD-95 binds to the N-methyl-D-aspartate receptor (NMDAR) subunit, and hence act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…Abnormally reduced PSD95 expression impairs activity‐dependent synaptic stabilization (Ehrlich, Klein, Rumpel, & Malinow, 2007), whereas PSD95 overexpression increases the excitatory to inhibitory synapses ratio and alters dendritic arbor development (Bustos et al., 2014; Prange, Wong, Gerrow, Wang, & El‐Husseini, 2004). PSD95 was dramatically reduced in the hippocampus of IUGR rats, similar to what has been described in animals exposed to perinatal hypoxia which also displayed impaired hippocampal maturation and deficits in spatial learning and memory (Chen et al., 2006, 2007). Abnormal PSD95 expression has also been associated with autism spectrum disorders in humans and animal models (Keith & El‐Husseini, 2008; Tsai et al., 2012), and these disorders have also been related to IUGR (Leonard et al., 2008; Walker et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormally reduced PSD95 expression impairs activity‐dependent synaptic stabilization (Ehrlich, Klein, Rumpel, & Malinow, 2007), whereas PSD95 overexpression increases the excitatory to inhibitory synapses ratio and alters dendritic arbor development (Bustos et al., 2014; Prange, Wong, Gerrow, Wang, & El‐Husseini, 2004). PSD95 was dramatically reduced in the hippocampus of IUGR rats, similar to what has been described in animals exposed to perinatal hypoxia which also displayed impaired hippocampal maturation and deficits in spatial learning and memory (Chen et al., 2006, 2007). Abnormal PSD95 expression has also been associated with autism spectrum disorders in humans and animal models (Keith & El‐Husseini, 2008; Tsai et al., 2012), and these disorders have also been related to IUGR (Leonard et al., 2008; Walker et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Synaptophysin is a presynaptic protein involved in synaptic vesicle biogenesis and trafficking that increases in parallel with the formation of synapses and is frequently used as an indicator of total synaptic vesicles pools (Valtorta et al., 2004). It is known that positive stimuli such as physical exercise and environmental enrichment increase synaptic proteins expression and normalize interneuron development, and are associated with improved synaptic plasticity and cognitive function (Abel & Rissman, 2013; Chen, Chen, Lei, & Wang, 1998; Chen et al., 2006; Hu, Ying, Gomez‐Pinilla, & Frautschy, 2009; Komitova et al., 2013). Therefore, it is possible that exercise inherent to water maze training might account for the synaptophysin normalization in IUGR rats after training such as what was observed in this study, and suggests that environmental management might reverse some of the synaptic changes associated with prenatal growth restriction postnatally.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that, using an animal model, experimentally perinatal hypoxia decreased pCREB and PSD-95 expression within the hippocampus (9,13). Thus, it highlights the possibility that such decreased expression could be a tentative therapeutic target for an alleviation of long-term neurological dysfunctions.…”
mentioning
confidence: 83%
“…On postnatal day 9 (P9), the animals were divided into four experimental groups as follows: vehicle-control, G-CSF alone, perinatal hypoxia, and G-CSF plus perinatal hypoxia rats, respectively. The procedures for inducing perinatal hypoxia were as described previously (9,13,25). It is generally accepted that rat pups of P10 to P12 roughly correspond to a term human infant (26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation